Host‐Specificity and Network Structure of Tick Microbiota in Co‐Distributed Species From the Iberian Peninsula - Víctor Noguerales; José de laFuente; Sandra Díaz‐Sánchez (Ecology and Evolution)
ABSTRACT Ticks are arthropods that have evolved a unique blood‐feeding lifestyle, making them intriguing subjects for exploring their adaptations to vertebrate hosts, their ability to transmit diseases, and their varied roles in the ecosystem. Despite the recent emphasis on the relevance of microbes in various aspects of tick biology (e.g., nutrition, metabolism, reproduction, survival, and competence), our understanding of microbial community variation across species and the underlying processes remains limited. Here, by integrating high‐throughput DNA sequencing with microbial ecological analyses and network association approaches, we investigate the community composition and structure of microbiota across natural populations of three co‐distributed tick species in the central Iberian Peninsula (Castilla‐La Mancha region). Our results revealed a complex and diverse microbiota, primarily composed of Proteobacteria, Bacteroidota, and Firmicutes. While all tick species exhibited a shared core microbiota, notable differences in microbial composition and network interactions suggest that each species may be influenced by ecological and evolutionary factors that shape their microbiota. These insights enhance our understanding of the complex relationships between ticks, their microbiota, and the surrounding environment, which can lead to improved strategies for managing vectors and controlling pathogens.